Radiocarbon dating of Sacred Ibis mummies from ancient Egypt. (December 2015) - Wasef, S.; Wood, R.; El Merghani, S.; Ikram, S.; Curtis, C.; Holland, B.; Willerslev, E.; Millar, C.D.; Lambert, D.M.
Abstract: Sacred Ibis ( Threskiornis aethiopicus ) were widespread in Egypt until the eighteenth century. Today the species is extinct in modern Egypt but millions of mummified specimens are scattered geographically in dedicated Ibis burial sites throughout the country. Ibises were regarded as physical manifestations of the god Thoth and worshiped by the ancient Egyptians. A small number of Sacred Ibis were chosen as 'sacred animals', based on physical markings, and were reared for the temples. However, the majority of the mummified Sacred Ibis were 'votive animals' that were given as offerings to the deities by pilgrims, and then buried in catacombs associated with the temple. Their supply became an industry that is thought to have flourished from the Late Period, well into the Roman Period (c. 664 BC to AD 350). Dating of the Sacred Ibis mummies, as well as other mummified animal specimens, has been based on archaeological evidence such as the age of catacombs, the design of enclosures and the shape of the mummy containers (pottery jars, wooden chests or stone boxes). Here we present the first ages of a selection of Sacred Ibis mummies using 14 C methods in order to establish how closely they match the archaeological chronology. Dates are reported from museum samples provenience from Saqqara, Roda and Thebes. Our 14 C radiocarbon results date the Ibis mummies between c. 450 and 250 cal BC and represent a short period of time. Those dates are falling from the Late Period to the Ptolemaic Period at maximum. Surprisingly, none of the samples were dated to the Roman era. Highlights: We present the first 14 C dates for animal mummified remains from Egypt in order to establish how closely they match the archaeological chronology. Our 14 C radiocarbon results date the Ibis mummies between c. 450 and 250 cal BC, which falls between the Late Period to the Ptolemaic Period at maximum and none of the samples were dated to the Roman era. In total one textile, one resinous substance and six bone samples were dated and the dates on textile and bone are consistent. We see no indication of a radiocarbon reservoir effect due to fresh water diet or contamination with mummification materials.